Hydrogen storage in magnesium hydride: The molecular approach - Harder, Sjoerd; Spielmann, Jan; Intemann, Julia; Bandmann, Heinz (Angewandte Chemie International Edition, 2011)
Big can be small: The largest ligand-stabilized magnesium hydride cluster, containing 8 Mg and 10 H ions, is a model for the smallest sub-nanometer-sized hydrogen storage material. This molecular cluster displays magnetic hydride-hydride coupling (see picture) and complete hydrogen desorption at the record-low temperature of 200 °C. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.